APPLICATION OF SKILLS ASKING TO TEACHERS TO IMPROVE SPEAKING ABILITY AND LIVING CHILDREN IN TK STATE DEVELOPMENT LEBONG (Study at Lebong Trustee State Kindergarten) - Budi Patresia; Nina Kurniah (UNIB Press, 2019)
This study aims to improve the skills of asking teachers to improve their speaking and listening skills to children in Lebong Kindergarten. This research was conducted because there were problems about the teacher's asking skills to improve the ability to speak and listen to children in Class B. The design of this study used a type of School Action Research (PTS) conducted collaboratively in two cycles, the subjects of this study were teachers of class B2 and B5 in State TK of Lebong Trustees. The data collection methods carried out in this study were training, observation and documentation. Data analysis techniques used are non-test techniques and data collection obtained from training in observation or observation and documentation. The results of the study obtained in this study that: the ability to speak and listen to children in the Lebong fostering kindergarten can be improved through the application of teacher asking skills.